Compulsory education in Singapore - Chim, Suan Yew (2008)
This study is conducted to analyze the level of acceptance of compulsory education in Singapore. The level of acceptance will be analyzed using the perception of effectiveness, benefits and drawbacks of compulsory education as bases. The study will also cover various issues that have arisen from the enactment of the Compulsory Education Act.